Life and Death in the Delta - Rogers, K. author. aut Link
X, 214 p. 20 illus.
Keywords: Terrorism, black poverty, and economic exploitation produced a condition of collective trauma and social suffering for thousands of black Deltans in the Twentieth Century. Based on oral histories with African American activists and community leaders, this work reveals the impact of that oppression.